The Curious Omission of Treatment as a Predictor of Pulmonary Sarcoidosis Mortality Response - Baughman, Robert P.; Lower, Elyse E.; Kirkil, Gamze (Elsevier Science Bv, 2018)
[Abstract Not Available]
Keywords: Corticosteroid-Therapy; Stage